COMPUTER SIMULATION OF COOPERATIVE ACTION OF CITICOLINE WITH METHYL-PREDNISOLONE PHARMACOTHERAPY IN MULTIPLE SCLEROSIS - Nefedov, А.A.; Mamchur, V.I.; Larionov, V.B.; Dronov, S.M. (World of Medicine and Biology, 2016)
Combined use of physiologically active compounds directed at optimizing their joint of pharmacotherapeutic effect. However, the successful use of combined dosage forms may be limited by the interaction of their constituents on physico-chemical, pharmaceutical and biological levels (pharmacological interaction) and requires a preliminary assessment of possible interactions and potential compatibility of certain pharmaceutical ingredients. We analyzed the results of their research, reflecting the comparative description of the impact of facilities of neuroprotective, antioxidant complex in neurological status, conditioned reflex activity, behavioral reactions of rats processes of energy and functional state of mitochondria of neurons in the cerebral cortex and histomorphometrical allowing the entities under the experimental equivalent multiple sclerosis. It is shown that the combined use of citicoline and methylprednisolone strongly reduces the severity of neurological disorders compared to the group receiving hormone therapy base. Analysis of the acid-alkaline properties was conducted using ACD / pKa DB. The molecular weight, solubility, hydrophobicity determined additive methods using computer programs. The presented combination of "methylprednisolone, citicoline" no possible interactions both on physical and chemical level (in a combination dosage form) and the pharmacokinetic level stages. Also on the joint use of citicoline methylprednisolone expect strengthening its stimulating action. Based on the difference in half-life, and indirect (indirectly through metabolic processes) mechanism of the therapeutic effect of the compounds examined, with pharmacokinetic standpoint of methylprednisolone combination of citicoline is safe and effective.
Keywords: multiple sclerosis; pharmacotherapy; pharmacokinetics; computer simulation